High‐Performance Visible‐Light‐Driven Pt/CdS/Graphene Photoelectrocatalysts for Methanol Oxidation. Issue 8 (22nd March 2017) - Zhai, Chunyang; Hu, Jiayue; Sun, Mingjuan; Zhu, Mingshan
Abstract: Fuel cells, as a technology for the conversion of chemical energy into electrical energy, have been recognized as a promising sustainable power source. Traditional electrocatalysts, together with optically active semiconductors, have been selected as promising catalysts for the improvement of anodic reactions. Herein, cadmium sulfide (CdS) nanoclusters decorated on reduced graphene oxide (RGO) nanosheets were obtained by using a one‐pot solvothermal method and then applied as photoactivated supports for the deposition of Pt nanoparticles. The ternary‐composite‐modified electrode displayed much higher catalytic properties for methanol oxidation than a binary Pt/CdS electrode. Interestingly, when the as‐prepared Pt/CdS/RGO electrode was irradiated with visible light, both the catalytic activity and the stability were improved greatly. The synergistic effect of RGO nanosheets and photoirradiation promoted electrocatalytic performance and stability. Our results provide new insight into the development of highly efficient photoelectrocatalysts for applications in direct methanol fuel cells in the presence of visible‐light illumination. Abstract : The power of three : A synergistic effect of RGO nanosheets and photoirradiation promotes the electrocatalytic performance of methanol oxidation under visible‐light irradiation.